Human physiology from cells to systems - Sherwood, Lauralee (Cengage Learning, 2016)
Organized around the central theme of homeostasis - how the body meets changing demands while maintaining the internal constancy necessary for all cells and organs to function, this book helps you appreciate the integrated functioning of the human body.